An investigation into the planning and design of neighbourhood playground towards the well-being of children in low cost apartments - Abdul Karim, Hafazah; Mohd Latfi, Muhammad Faez (2011)
The well being of residents in urban areas highly depends on the quality of the housing environment. Quality of life is really a matter of the well-being of the residents that include the comfort and convenience of all age-group in all socioeconomic levels especially for the low income earners. This is actually part of the community goals for the local authority of any particular housing estates in urban areas. In realizing these goals the local authority have drawn up planning guidelines for every aspects of the physical environment within their control such as infrastructure and amenities which include housing, landscaping, commercial, open spaces and recreation. Therefore, to achieve a harmonious living environment, development and growth of a residential area should not rely on the provision of building design alone. One of the many important factors is the effectiveness aspect in the planning and the suitability of the provision of children playground in the low cost residential areas. The main concern is the lack of proper playing areas such as playgrounds and adequate playing equipment's for the children living in low cost flats as had been found by a study in Shah Alam and Klang (Abdul Karim, H., 2008). The inadequacy and insufficiency of these facilities is questioned because there seems to be minimal provision whereas it was found that there are a large number of children living in this type of housing. Findings from that study also found that there are many incidences of bullying and fighting due to the competition for playing equipment's and spaces. This problem affect the well-being of children directly and the parents of the affected children indirectly. Therefore although the children living in the study area is not without places to play such as playgrounds and open spaces the question posed here are the adequacy and the sufficiency of playing spaces and facilities that are provided by the Local Authority towards the well-being of children.